2021
DOI: 10.3390/w14010059
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multi-Layered Structure of Vadose Zone on Ecological Effect of Groundwater in Arid Area: A Case Study of Shiyang River Basin, Northwest China

Abstract: The natural vegetation in arid areas of northwest China is strongly dependent on the availability of groundwater. Significantly, capillary water plays an essential role in regulating the ecological groundwater level in the multilayered structure of the vadose zone. The soil-column test and field survey in the lower reaches of the Shiyang River Basin were conducted to investigate the influence of the multi-layered structure of the vadose zone on maintaining the ecological effect of groundwater. Based on the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The suitable groundwater depth for Populus euphratica is 3-5 m, and its stress water level is 6-8 m [54]. This is generally consistent with the pattern depicted in Figure 11, where NDVI shows a positive correlation with groundwater depths below 4 m and NDVI shows a negative correlation with groundwater depths above 4 m. Due to the low rainfall in arid areas such as the study area, groundwater is an important resource for supporting the growth of vegetation; however, the uncontrolled exploitation of groundwater will inevitably destroy the stability of the groundwater flow field in the natural vegetation area, meaning that the depth of the groundwater will continue to increase, resulting in drought stress of natural vegetation and even large-scale extinction [51,54].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The suitable groundwater depth for Populus euphratica is 3-5 m, and its stress water level is 6-8 m [54]. This is generally consistent with the pattern depicted in Figure 11, where NDVI shows a positive correlation with groundwater depths below 4 m and NDVI shows a negative correlation with groundwater depths above 4 m. Due to the low rainfall in arid areas such as the study area, groundwater is an important resource for supporting the growth of vegetation; however, the uncontrolled exploitation of groundwater will inevitably destroy the stability of the groundwater flow field in the natural vegetation area, meaning that the depth of the groundwater will continue to increase, resulting in drought stress of natural vegetation and even large-scale extinction [51,54].…”
Section: Discussionmentioning
confidence: 93%
“…Due to the specific climatic characteristics of arid zones with scarce rainfall and strong evaporation, the vegetation relies heavily on groundwater for evapotranspiration [50,51]. As shown in Figure 16, the correlation coefficients between the multi-year average depth of groundwater and NDVI in the irrigation area were in the range of −0.987~0.987.…”
Section: Discussionmentioning
confidence: 99%
“…Groundwater plays an indispensable role as a crucial regulator of water, salt, and heat in shallow soil, maintaining the equilibrium of these factors within plant habitats, even in deep buried areas (Mata‐González et al, 2022). Moreover, some researchers have demonstrated that vertical interactions among “groundwater‐soil‐vegetation” significantly contribute to eco‐environmental processes (Cao et al, 2021: Cui et al, 2022; Yin et al, 2021). However, human activities have led to the decline in groundwater levels seriously for nearly half a century, which have become an important factor affecting the ecological function and evolution of regional surface ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…even in deep buried areas (Mata-González et al, 2022). Moreover, some researchers have demonstrated that vertical interactions among "groundwater-soil-vegetation" significantly contribute to eco-environmental processes (Cao et al, 2021: Cui et al, 2022Yin et al, 2021).…”
mentioning
confidence: 99%